READINESS DESA DIGITAL: STUDI DI DESA TUMBANG PENYAHUAN - Setianingsih Setianingsih; Bagas Rizky Ardiansyah; Suprayitno Suprayitno; Subhan Ilham Thareq (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2026)
This study aims to analyze the readiness for digital village implementation in Tumbang Penyahuan Village using the Readiness for Change framework, which encompasses individual, organizational, and structural dimensions. The study employed a qualitative approach with a single case study design to gain a contextual understanding of the dynamics of digitalization at the village level. Data were collected through in-depth interviews, observation, and documentation with seven key informants. From the individual dimension, village officials possess basic skills and positive attitudes toward digitalization, but are still limited to administrative operational use. From the organizational dimension, digitalization has driven increased coordination and work efficiency, although it has not yet been fully integrated into the organizational culture. From the structural dimension, digital infrastructure is relatively available, but its effectiveness depends on electricity stability. These findings suggest that the primary constraint is not infrastructure availability, but rather human resource capacity and organizational integration. Theoretically, this study reinforces the argument that readiness is not solely technical, but rather a multidimensional construct influenced by interactions between actors, organizations, and systems. Practically, the results emphasize the importance of strengthening digital competencies and institutional integration strategies in digital village implementation. Keywords: , Digitalization; Digital Village; Governance; Readiness For Change